CO2 capture and attrition performance of competitive eco-friendly calcium-based pellets in fluidized bed - Su, Chenglin; Duan, Lunbo; Anthony, Edward J. (Wiley, 2018)
A system incorporating spent bleaching clay (SBC) into the calcium looping (CaL) process has been proposed. In this paper, prepared sorbents doped with regenerated SBC and cement were tested in a bubbling fluidized bed (BFB) to examine in detail their cyclic CO2 capture capacity and attrition properties. The results revealed that the cyclic CO2 capture capacity of pellets modified by pyrolyzed SBC and/or cement showed significantly better performance than limestone, which is consistent with the thermogravimetric analyzer (TGA) results. This is due to the improvement of pore structure and enhanced sintering resistance created by adding support materials to the sorbent. The elutriation rates of the composites prepared with pyrolyzed SBC and/or cement were consistently lower than for crushed limestone. Scanning electron microscopy (SEM) images indicated that the pellets possessed higher sphericity than limestone particles, thus reducing surface abrasion. Limestone exhibited a high attrition rate (diameter reduction rate) of 10.7 μm/cycle, which could be eliminated effectively by adding regenerated SBC and/or cement. ‘L‐5PC‐10CA’ (85% lime/5% pyrolyzed SBC/10% cement) exhibited an attrition rate of only 7.9 μm/cycle. Based on the analysis of breakage and probability density function (PDF) for particle size distribution, it appeared that pellets without cement experienced breakage (mostly chipping and disintegration) and surface abrasion, whereas ‘L‐10CA’ (90% lime/10% cement) and ‘L‐5PC‐10CA’ mainly suffered surface abrasion, combined with some chipping.
Keywords: CO 2 capture; calcium looping; CaO‐based sorbent; spent bleaching clay regeneration; attrition